RESEARCH ON ENGLISH TEACHING REFORM IN HIGHER VOCATIONAL COLLEGES BASED ON NATIONAL VOCATIONAL COLLEGE ENGLISH SPEAKING CONTEST - Li, Mingjun; Long, Zhiyong; He, Yan (International Journal of Research -GRANTHAALAYAH, 2025)
The National Vocational College English Speaking Contest has been playing a leading role in the English teaching reform in higher vocational colleges in China. The Contest mainly consists of five sections, i.e. Presentation, Interview, Debate, Role-Play and Speech. By analyzing each section, it is clearly shown that the competencies examined in the Contest align closely with that of the English teaching reform. However, the problems exposed by the contestants also deserve our attention, which helps identify the challenges in current higher vocational English teaching, including weak English foundation, insufficient communication awareness, limited critical thinking ability, inability to adapt effectively in real-time, etc. Combining the positive effects the Contest brings and the problems the contestants exposed, the article suggests updating teaching philosophies, improving teaching methods, expanding teaching resources and optimizing teaching assessments to promote higher vocational English teaching reform.